The Fundamental Properties and Biocompatibility Classification of Extraoral Prosthesis: A Review (Journal of Medical Device Technology, 2023)
This review article discusses on fundamentals of extraoral prosthesis and concerns on the biocompatibility classifications of extraoral prosthesis as medical device. Maxillofacial prosthodontics is a field that seldom being explored. Due to the circumstances, the progression and evolution of research of this area for evidence-based practice are slower comparing to another dental field. Hence, the purpose of this paper is to contribute and provide additional scientific knowledge in related field. Electronic search was done on several databases with keywords ‘maxillofacial prostheses and ‘biocompatibility’. In general, maxillofacial prosthesis can be divided into extraoral prosthesis, intraoral prosthesis, or combination of both depending on the location and function. Ideal properties can be divided into ideal processing characteristics, ideal biologic properties, and ideal physical and mechanical properties of processed extraoral prosthesis materials. Extraoral prosthesis can be classify as Class I or Class II depending on the retentive system according to FDA, and USP Class I and Class III depending on the underlying tissue.
Keywords: Maxillofacial Prosthesis; Biocompatible Materials; Review Literature